Birbs without wings - De Bernieres, Louis, 1954- (Quality Paperbacks Direct, 2004)
The destruction of the Ottoman empire in the first world war and its aftermath put an end to a tradition of religious and ethnic tolerance in Asia Minor, the Balkans and the Arab lands. In place of the corrupt but uninquisitive old order, a half-domesticated nationalism ruined the old cosmopolitan cities of the eastern Mediterranean - Istanbul, Salonika, Smyrna, Beirut, Alexandria - broke up any affinities between Muslims, Christians and Jews, and undermined every effort to establish liberal and prosperous states. There has been a century of war.